2022
DOI: 10.1186/s12909-022-03349-z
|View full text |Cite
|
Sign up to set email alerts
|

Developing an innovative medical ethics and law curriculum—constructing a situation-based, interdisciplinary, court-based learning course: a mixed methods study

Abstract: Background Traditional lecture-based medical ethics and law courses deliver knowledge but may not improve students’ learning motivation. To bridge this theory-to-practice gap and facilitate students’ learning effectiveness, we applied situated-learning theory to design an interdisciplinary court-based learning (CBL) component within the curriculum. Our study aimed to investigate students’ learning feedbacks and propose a creative course design. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…27 In addition, 70% of medical students who were taught medical law through an innovative curriculum agreed that the course was useful. 28 Teaching medical students about pertinent information regarding medical malpractice and the law may help mitigate their fear about medical malpractice, and have them eventually learn practices that may help prevent lawsuits. In addition, students are open to the idea of learning about medicolegal topics, as they believe that the information will be essential to becoming a physician.…”
Section: Resultsmentioning
confidence: 99%
“…27 In addition, 70% of medical students who were taught medical law through an innovative curriculum agreed that the course was useful. 28 Teaching medical students about pertinent information regarding medical malpractice and the law may help mitigate their fear about medical malpractice, and have them eventually learn practices that may help prevent lawsuits. In addition, students are open to the idea of learning about medicolegal topics, as they believe that the information will be essential to becoming a physician.…”
Section: Resultsmentioning
confidence: 99%
“…Another avenue which was demanded by at least one half of the participants in this study for medical curriculum enrichment, was developing a more dynamic education of ethics and law in medicine. This approach is needed for building appropriate rapport between medical doctors and their patients meanwhile understanding of the legal complexities which are inherent in medical practice, as also another study concluded [ 22 ]. Our study also found that lack of empowerment of medical students in anger management is another existing gap in the current medical curriculum, as also resulted by another study [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, medical education should steer toward systematically developing programs for medical law education [ 35 ], while pertinent training courses can be integrated into undergraduate, postgraduate, and continuing education. For example, medico-legal education, such as court-based learning, visiting actual courts, and creating opportunities to communicate with legal professionals, can help students enrich their knowledge in medical ethics and law and remove negative stereotypes about medical disputes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%